PENGARUH PERANG RUSIA-UKRAINA TERHADAP EKONOMI INTERNATIONAL - Prasetyo, Totok Adhi; Syah, Nadya Faza Malika; Ghofari, Aqil; Aidah, Noer; Faruq, Umar; Mirzak, Marisa; Khatimah, Dyanul (At-Tawazun, Jurnal Ekonomi Syariah, 2024)
This research aims to determine the influence of the Russian-Ukrainian war on the international economy and its impact on the economy in Southeast Asia. The research method used in this research is a qualitative method with a library research approach which examines various published literature related to the economic impact that emerged as a result of the Russian and Ukrainian war conflict. The results show that the Russian and Ukrainian War has had an impact on the international economy, especially on countries that depend on Russia and Ukraine for food and energy supplies. Disruptions to the global supply chain due to this war caused a spike in commodity prices such as oil, gas, and food, which resulted in increased inflation in various countries, including Southeast Asian countries.